Shaping the heart: Structural and functional maturation of iPSC-cardiomyocytes in 3D-micro-scaffolds. (January 2020) - Silbernagel, Nicole; Körner, Arlene; Balitzki, Jakob; Jaggy, Mona; Bertels, Sarah; Richter, Benjamin; Hippler, Marc; Hellwig, Andrea; Hecker, Markus; Bastmeyer, Martin; Ullrich, Nina D.
Abstract: Cardiomyocytes derived from induced pluripotent stem cells (iPSC-CMs) represent the best cell source for cardiac regenerative purposes but retain an immature phenotype after differentiation with significant limitations compared to adult cardiomyocytes. Apart from an incomplete cardiomyocyte-specific structure and microarchitecture, cells show at the level of Ca 2+ signaling only slow Ca 2+ release and reuptake properties. Here, we investigated the effect of restructuring single iPSC-CMs in specially designed 3D-micro-scaffolds on cell morphology and Ca 2+ handling. Using direct laser writing, rectangular-shaped scaffolds were produced and single iPSC-CMs were seeded into these forms. Structural analyses revealed strong sarcolemmal remodeling processes and myofilament reorientation in 3D-shaped cells leading to enhanced clustered expression of L-type Ca 2+ channels and ryanodine receptors and consequently, to faster Ca 2+ transient kinetics. Spontaneous beating activity was enhanced and Ca 2+ handling was more robust compared to non-patterned cells. Overall, our data demonstrate for the first time significant improvement of Ca 2+ signaling properties in reshaped iPSC-CMs indicative of functional maturation by structural remodeling.